Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. **There will be no changes to other Yahoo properties or services, or your Yahoo account.** You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

## Trending News

# Multiply and simplify?

( x + 6 )( x3 – x2 – 5x + 1 )

### 3 Answers

- Mathy KathyLv 51 decade agoFavorite Answer
Its almost like FOIL, you just multiply everthing in the second factor by the first term in the first factor, then do it again with the second term in the first factor, then combine like terms:

( x + 6 )( x3 – x2 – 5x + 1 ) Multiply the second factor by x:

First: x*x^3=x^4

Second: x*-x^2= -x^3

Third: x*-5x= -5x^2

Last: x*1= x

Now the second term, 6:

First:6*x^3=6x^3

Second:6* -x^2= -6x^2

Third: 6* -5x= -30x

Last: 6*1= 6

Now make the string of terms:

x^4-x^3-5x^2+x+6x^3-6x^2-30x+6

And combine like terms:

x^4+5x^3-11x^2-29x+6 and that's all you can do.

wpf.

- Anonymous1 decade ago
(x)(x^3 - x^2 - 5x + 1) = x^4 - x^3 - 5x^2 + x

(6)(x^3 - x^2 - 5x + 1) = 6x^3 - 6x^2 - 30x +6

So (x+6)(x^3 - x^2 - 5x + 1) = x^4 + 5x^3 - 11x^2 - 29x + 6

Source(s): I'm a math major